Research advances in the regulation of the putative ovarian germline stem cell niche on female germline stem cells. (4th March 2019) - Liu, Yangchun; Xu, Jiao; Zhu, Feiyin; Ye, Haifeng; Hu, Chuan; Huang, Jian; Zheng, Yuehui
ABSTRACT: Stem cells are ideal seeding cells, which have the potential for self-renewal and multiple differentiation, and they play a fundamental role in maintaining homeostasis and regenerating and repairing tissue. The discovery of female germline stem cells (FGSCs) brings much hope for the postnatal renewal of oocytes and solving some female infertility problems. Ovarian function declines with increasing female age. Moreover, ovarian germline stem cell niche-aging could be the main cause of ovarian senescence, which ultimately leads to decreased follicle generation, declining female fertility, and age-related diseases, such as osteoporosis and ovarian cancer. The ovarian germline stem cell niche is the surrounding microenvironment in which FGSCs live, and it helps control the biological characteristics of FGSCs in many ways, such as nutritional supply and immunological cytokine secretion. This paper reviews the knowledge about the ovarian germline stem cell niche and its probable regulatory mechanisms on FGSCs, which provides valuable scientific information and scope for the prevention and treatment of ovarian senescence. Abbreviations: BMP: bone morphogenetic protein; Dpp: decapentaplegic; FGSC: female germline stem cell; IL, interleukin; OGSC: ovarian germline stem cells; ROS: reactive oxygen species; TGF, transforming growth factor; TNF, tumor necrosis factor